Vulvar sarcoma outcomes by histologic subtype: a Surveillance, Epidemiology, and End Results (SEER) database review. Issue 8 (7th July 2020) - Johnson, Sarah; Renz, Malte; Wheeler, Lindsay; Diver, Elisabeth; Dorigo, Oliver; Litkouhi, Babak; Behbakht, Kian; Howitt, Brooke; Karam, Amer
Abstract : Objective: Vulvar cancers account for 5% of all gynecologic malignancies; only 1%–3% of those vulvar cancers are primary vulvar sarcomas. Given the rarity of vulvar sarcomas, outcome data specific to histopathologic subtypes are sparse. The aim of this study was to identify clinical and pathologic factors of primary vulvar sarcomas that are associated with survival and may inform treatment decisions. Methods: The Surveillance, Epidemiology, and End Results (SEER) database was searched for women diagnosed with vulvar sarcoma between 1973 and 2018. We identified 315 patients and reviewed their demographic, clinicopathologic, surgical, and survival information. Statistical analyses included χ 2 and t-tests, Kaplan–Meier survival, and Cox regression analyses. Results: The most common histopathologies of vulvar sarcomas were dermatofibrosarcomas (85/315, 27%) and leiomyosarcomas (72/315, 22.9%). Rhabdomyosarcomas (18/315, 5.7%), liposarcomas (16/315, 5.1%), and malignant fibrous histiocytomas (16/315, 5.1%) were less frequent. The majority of patients underwent surgery (292/315, 92.7%), which included lymph node dissections in 21.6% (63/292). Survival and lymph node involvement varied significantly with histologic subtype. The 5-year disease-specific survival for dermatofibrosarcomas, liposarcomas, and fibrosarcomas was 100% and only 60.3% and 62.5% for malignant fibrous histiocytomas and rhabdomyosarcomas, respectively. None of the patients with (dermato)fibrosarcomas, liposarcomas, or leiomyosarcomas had positive lymph nodes, in contrast to rhabdomyosarcomas and malignant fibrous histiocytomas with 77.8% and 40% positive lymph nodes, respectively. The 5-year disease-specific survival for women with positive lymph nodes was 0%. Conclusions: Vulvar sarcomas are heterogeneous with survival highly dependent on the histopathologic subtype. While surgical excision is the mainstay of treatment for all vulvar sarcomas, staging lymphadenectomy should be deferred for (dermato)fibrosarcomas, liposarcomas, and leiomyosarcomas as there were no cases of lymph nodes metastases.